Silver Nanoparticles as a selective probe for Mercury Ions: A Review - Farhan, Safana Ahmed (Iraqi Journal of Science, 2022)
Nanochemistry is a significant area which involves the synthesis, design, and manipulation of particle structures with dimensions ranging from 1 to 100 nanometres. It is now one of the major concerns of pharmaceutical and biological researchers. The current study discusses recent advances in the use of silver nanoparticles (AgNPs) as a selective sensor for qualitative and colorimetric quantitative detection of mercury ions.   The synthesis of significant noble metal AgNPs is described as a novel, low-cost, quick, and simple method for detecting mercury ions. Due to the seriousness of mercury toxicity to our cells, AgNPs may be successfully employed for the detection of ecologically harmful mercury ions in a wide variety of aqueous practical samples using a colorimetric approach. As a result, as provided in this review with extensive details regarding this analytical approach, it might be utilized to monitor mercury ions via AgNPs in a variety of practical samples.